Market Entry Analysis of Toro Capital on the United States Natural Gas Market - Popa, Laura Adelina (2011)
This study is an attempt of valuable contribution to the alternative investment market entry modes since it presents the case of Toro Capital, a Swiss-based company, willing to start its trading operations in the United States natural gas market. Having in mind the highly competitive business arena in this industry, it is of particular interest how a foreign company is able to enter the United States and benefit from similar advantages as local companies.